Effectiveness of an Adapted Diabetes Prevention Program Lifestyle Intervention in Older and Younger Adults. Issue 6 (1st June 2015) - Brokaw, Sarah M.; Carpenedo, Dorota; Campbell, Paul; Butcher, Marcene K.; Furshong, Ginny; Helgerson, Steven D.; Harwell, Todd S.; the Montana Cardiovascular Disease and Diabetes Prevention Workgroup
<x xml:space="preserve">Abstract</x> Objectives To compare participation, self‐monitoring behaviors, and weight loss outcomes in older and younger participants in an adapted Diabetes Prevention Program (DPP) lifestyle intervention. Design Pre‐ and postevaluation of outcomes in participants enrolled in the Montana Cardiovascular Disease (CVD) and DPP lifestyle intervention from 2008 through 2012. Setting Community. Participants Adults at high risk for CVD and type 2 diabetes mellitus (N = 3, 804). Measurements Number of core (16 weekly sessions) and postcore (6 monthly sessions) intervention sessions attended, weekly self‐monitoring of fat intake and minutes of physical activity, weight loss outcomes and achievement of the weight loss goal, and improvements in CVD‐related risk factors. Results Participants aged 65 and older were significantly more likely to attend more intervention sessions, self‐monitor their fat intake, and achieve the physical activity and weight loss goals than those younger than 65. Older and younger participants experienced significant improvements in CVD‐related risk factors. Conclusion Older adults at high risk of CVD and diabetes mellitus participating in an adapted DPP lifestyle intervention had higher participation and self‐monitoring rates than younger participants, were more likely to achieve physical activity and weight loss goals, and achieved similar CVD risk reduction.